2014
DOI: 10.1186/preaccept-7285495961101327
|View full text |Cite
|
Sign up to set email alerts
|

A simple metric of promoter architecture robustly predicts expression breadth of human genes suggesting that most transcription factors are positive regulators

Abstract: Background: Conventional wisdom holds that, owing to the dominance of features such as chromatin level control, the expression of a gene cannot be readily predicted from knowledge of promoter architecture. This is reflected, for example, in a weak or absent correlation between promoter divergence and expression divergence between paralogs. However, an inability to predict may reflect an inability to accurately measure or employment of the wrong parameters. Here we address this issue through integration of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 32 publications
(42 reference statements)
3
32
0
Order By: Relevance
“…We further speculate that this mechanism is also involved in gene repression during other transitions like cellular differentiation, which would be consistent with the notion that most mammalian transcription factors are activating (Hurst et al 2014).…”
Section: Tnf-induced Adipocyte Inflammationsupporting
confidence: 89%
“…We further speculate that this mechanism is also involved in gene repression during other transitions like cellular differentiation, which would be consistent with the notion that most mammalian transcription factors are activating (Hurst et al 2014).…”
Section: Tnf-induced Adipocyte Inflammationsupporting
confidence: 89%
“…A complete list of this dataset is available at Additional file 1 : Table S1. Since many reports have also used a window that flanks the TSS of known genes [ 16 , 17 ], we have also defined a different window of same size (5 KB) now encompassing 2,5 KB in each side of a given TSS. For this window, we found that 9,733 human genes had at least one TFBS affected by a polymorphic INDEL in the 1000 Genomes dataset (with a total of 69,959 TFBS affected by indels and 14,665 TFBS-ID).…”
Section: Resultsmentioning
confidence: 99%
“…A correlation between the size of promoter architecture and the breadth of expression was detected. Transcription factors with the strongest contribution to housekeeping expression were identified [ 10,11] Anti-reductionist Signaling pathway (33 animal genomes were surveyed)…”
Section: Strategymentioning
confidence: 99%